Excretion of Pu-238 during Long-term Chelation Therapy by Repeated DTPA Inhalation. Issue 3 (20th September 2022) - Grémy, Olivier; Blanchin, Nicolas; Miccoli, Laurent
Abstract: An individual underwent an extensive diethylenetriaminepentaacetate (DTPA) chelation therapy that started several months after plutonium incorporation, most likely by inhalation of a soluble compound. After receiving multiple intravenous infusions of DTPA, the patient continued the treatment by pulmonary delivery of aerosolized DTPA. The purpose of the present work is to provide and discuss the bioassay data obtained during the DTPA aerosol therapy and compare them with those under the DTPA infusion therapy that have been largely interpreted elsewhere. As with DTPA given intravenously, each delayed DTPA inhalation increased the clearance of plutonium not only in urine but also in feces, thus demonstrating the ability to remove plutonium retained by extrapulmonary tissues. Also, the slow decline of increased plutonium urinary elimination together with enhanced fecal excretion are two features coherent with the contribution of intracellular chelation to overall decorporation. The therapeutic benefit of DTPA inhalation appeared lower than with DTPA infusion, most likely due to a lower amount of DTPA reaching the systemic compartments where plutonium chelation predominates. The results suggest that DTPA administration through aerosol could be an alternative to the invasive procedure using a needle, i.e., intravenous injection/infusion, when protracted decorporation therapy is needed following transuranic internalization. Indeed, the patient may be more inclined to undergo a chelation treatment for a longer period because taking DTPA by inhalation may make it less cumbersome and painful.